2015
DOI: 10.1111/corg.12117
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Business Case: The Need for Both Utility and Justice Rationales for Increasing the Share of Women on Boards

Abstract: Manuscript type: EmpiricalResearch Question: In the context of the recent introduction of gender representation regulations (quotas) for boards in public limited companies (PLCs) in Norway, this article explores how gender quotas designed to increase the share of women in senior positions are rationalized and/or justified by those who benefit, and asks: what arguments do the beneficiaries of quotas tend to use when discussing their usefulness? Research Findings/Insights: Drawing on qualitative interview data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
87
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 77 publications
(128 reference statements)
5
87
0
4
Order By: Relevance
“…Legislative quotas have been described as “motors of change” (European Commission, , p. 1) and appear to be working, with Norway having achieved a female representation of approximately 42% on the boards of listed organizations (Terjesen et al, ). However, when quotas were first introduced in Norway, private‐sector managers, politicians, and the media were quick to openly voice their opposition, including assertions that quotas would ruin the Norwegian economy (Huse & Seierstad, ; Seierstad, ). Norway is now seen as a success story, with women appointed to boards under the Norwegian quota system recognized as highly qualified and competent individuals who are replacing mediocre men (Huse & Seierstad, ; Seierstad, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Legislative quotas have been described as “motors of change” (European Commission, , p. 1) and appear to be working, with Norway having achieved a female representation of approximately 42% on the boards of listed organizations (Terjesen et al, ). However, when quotas were first introduced in Norway, private‐sector managers, politicians, and the media were quick to openly voice their opposition, including assertions that quotas would ruin the Norwegian economy (Huse & Seierstad, ; Seierstad, ). Norway is now seen as a success story, with women appointed to boards under the Norwegian quota system recognized as highly qualified and competent individuals who are replacing mediocre men (Huse & Seierstad, ; Seierstad, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, when quotas were first introduced in Norway, private‐sector managers, politicians, and the media were quick to openly voice their opposition, including assertions that quotas would ruin the Norwegian economy (Huse & Seierstad, ; Seierstad, ). Norway is now seen as a success story, with women appointed to boards under the Norwegian quota system recognized as highly qualified and competent individuals who are replacing mediocre men (Huse & Seierstad, ; Seierstad, ).…”
Section: Introductionmentioning
confidence: 99%
“…They are therefore more open to diverse opinions, more willing to ask controversial questions and less likely to resort to 'group thinking' (Natesan 2013 Gul, Hutchinson and Lai (2013) found that gender diverse boards reported financial performance in a more transparent and accurate manner than male-dominated boards. A positive business case for board gender diversity (also referred to as the utility argument) was observed by several authors (Adams & Ferreira 2009;Seierstad 2016;Simpson, Carter & D'Souza 2010). In addition to financial benefits, gender diverse boards are associated with proactive social and environmental policies, practices and reporting (Bernardi & Threadgill 2010;Glass, Cook & Ingersoll 2015).…”
Section: Benefits Concerns and Possible Reasons For The Low Level Ofmentioning
confidence: 87%
“…Arguments for enhanced female board representation range from a moral imperative claiming that it is the 'right thing to do' (Robinson & Dechant 1997) to reasoning that it is the 'bright thing to do' (Terjesen, Sealy & Singh 2009). The former claim centres on the notions of social justice, fairness and equality, while the latter is based on the strategic and financial benefits of board gender diversity (Farrell & Hersch 2005;Seierstad 2016). …”
Section: Benefits Concerns and Possible Reasons For The Low Level Ofmentioning
confidence: 99%
See 1 more Smart Citation